Penggunaan Strategi Pembelajaran Inkuiri dalam Meningkatkan Kemampuan Berfikir Kritis Peserta Didik - Thifa Ramadhani; Liola Sinta; Gusmaneli Gusmaneli (Journal of Creative Student Research, 2024)
This research discusses inquiry learning strategies used to improve students' critical thinking skills. Inquiry is a method that allows students to discover knowledge for themselves through a process of investigation and analysis. In this research, the author uses a qualitative approach to understand how inquiry strategies can improve students' critical thinking skills. This research shows that inquiry strategies can improve students' critical thinking skills by enabling them to think critically and analytically. In this way, students can develop more effective thinking skills and improve their ability to solve problems. In this research, the author also found that inquiry strategies can improve students' critical thinking skills by enabling them to actively participate in the learning process. In this way, students can develop more effective thinking skills and improve their ability to solve problems.